Analisis SIA Terhadap Penjualan Obat Pasien Umum di Rumah Sakit Pusri Palembang - M. Rifqi Arsyi; Usnia Wati Keristin (Universitas Multi Data Palembang, 2026)
This study aims to analyze the SIA for general patient drug sales at Pusri Hospital in Palembang, which uses the Neural Universal Healthcare Application (NUHA) system. This study used a qualitative approach with descriptive methods. Data were obtained through in-depth interviews, observations, and documentation in the pharmacy, cashier, and finance units. The results indicate that the NUHA system has been used to support the integrated medicine sales and transaction recording process. However, the SIA is not yet fully optimal because several obstacles still impact the smoothness of medicine sales and the quality of service to patients. This study discusses these obstacles and the efforts that can be made to overcome them. It is hoped that this system can be used as material for evaluation and development of SIA in the future.